Purification of supercoiled HPV-16 E6/E7 plasmid using a modified monolithic support - Amorim, Lúcia Filipa Alves (2014)
About 15% of human cancers are caused by viruses. For instance, the particular case of the high-risk human papillomavirus (HPV) is associated with more than 99% of cervical carcinomas. The preventive vaccines for HPV infection available in the market only induce the antibody immunity and are completely ineffective when the infection is already present. Therefore, the problematic associated to HPV infections and tumor progressions continue to be unsolved. Thus, the urge to attenuate the HPV associated lesions led to the development of DNA vaccines. DNA vaccines emerged as a versatile strategy to induce both humoural and cellular immune immune responses. In addition, plasmid DNA (pDNA) arose as a promising vehicle for gene delivery, due to its simple manufacturing process with high purity degree and low cost, as well as its ability to transfect eukaryotic cells with satisfactory expression levels. Therefore, in the last years, the growing demand of pharmaceutical-grade pDNA fostered the development of new chromatographic supports, allowing high capacity and selectivity by the supercoiled (sc) pDNA. The innovative monolithic matrices are considered advantageous supports to purify large biomolecules, such as pDNA, due to their tridimensional characteristics of interconnected pores, which allows good mass transfer properties and binding capacity. Amino acid-affinity chromatography has revealed to be a promise approach that selectively recognizes the sc pDNA, since this strategy is based on natural occurrence of multiple interactions between proteins and nucleic acids in biological organisms, which mainly involve basic amino acids such as L-histidine. Surface Plasmon Resonance (SPR) Biosensor can be used to exploit the interactions between immobilized amino acids and different plasmid topologies to provide further structural information for affinity chromatography purification. Thus, the aim of this work was to perform a screening of L-histidine amino acid and their derivatives, Im-benzyl-L-histidine and L-methyl-L-histidine, employing the SPR technique in order to modify a monolithic support with the selected ligand, to purify pDNA. Several experiments were performed with three plasmids of different sizes (6.05, 8.70 and 14 kilo base pairs) and different isoforms (open circular, sc and linear), separately. The results revealed that the overall affinity of plasmids to L-histidine ligand and their derivatives was high (KD >10-8 M) and the highest affinity was found for HPV-16 E6/E7/L-histidine interaction, 3.34 x 10-10 ± 0.0209 M. Therefore, L-histidine was selected for immobilization on a monolithic matrix. After preparation of the histidine monolithic support, chromatographic studies were also accomplished with the aforementioned samples. In general, the sc isoform developed strong interactions with the support and the separation of plasmid isoforms was achieved by decreasing ammonium sulfate concentration. The separation of plasmid isoforms remained unchanged by flow rate variations. The breakthrough experiments of L-histidine monolith revealed satisfactory dynamic binding capacity when compared to other matrices. Overall, affinity chromatography can benefit from affinity analysis experiments provided by SPR biosensor, and the combination of L-histidine ligand with the monolithic support can be a promising strategy to purify the sc pDNA with the desirable purity degree for pharmaceutical applications, such as the DNA vaccines directed against the HPVs.